PENERAPAN CORPORATE GOVERNANCE DALAM PENGELOLAAN RISIKO SOSIAL DAN LINGKUNGAN DI INDUSTRI PERTAMBANGAN (STUDI KASUS PT. FAJAR SAKTI PRIMA) - Dewi Santriani, Bunga Ratu Portuna; Asfiyah, Nurul (Jurnal Manajemen, 2025)
The implementation of Corporate Governance (CG) in managing social and environmental risks is a strategic step aimed at creating responsible, transparent, and sustainable company operations. This study aims to analyze the implementation of Corporate Governance principles at PT Fajar Sakti Prima, especially in managing social and environmental risks. The CG principles applied include transparency, accountability, responsibility, independence, and fairness. This implementation is realized through the establishment of a governance structure, the implementation of policies based on international standards (ISO 14001 and SMK3), and stakeholder engagement. The results of the study show that PT Fajar Sakti Prima has adopted a social and environmental risk management policy that is integrated with the principles of Corporate Governance. The company has formed a Governance and Risk Committee, as well as a special social and environmental management division that is directly responsible to the board of directors and board of commissioners. The environmental management strategy is carried out through post-mining land reclamation activities, waste management, and carbon emission control. Meanwhile, social risk management focuses on the management of indigenous peoples' rights, community participation in decision-making, and community empowerment through corporate social responsibility (CSR) programs.